The Effectiveness of the GGE and Clis Models Assisted by the Jarimatika Method on Motivation and Mathematics Learning Outcomes of Third Grade Elementary School Students - Astuti, Juan; Selvi, Nurhayati; Rahmawati, Rahmawati (Devotion : Journal of Research and Community Service, 2026)
This research is motivated by the essential issue of low motivation and learning outcomes in Mathematics at the elementary school level, particularly in the Woha District area. This phenomenon requires innovative interventions in the selection of learning models that can create an interactive, collaborative, and enjoyable learning environment for students. Therefore, the main objective of this study is to test the comparative effectiveness between the Group to Group Exchange (GGE) learning model and the Children Learning in Science (CLIS) learning model, integrated with the Jarimatika method as a supporting variable, and to analyze the interaction of these three factors on students’ motivation and mathematics learning outcomes. This quantitative study employed a 2×2 factorial experimental design involving 36 third-grade students from two elementary schools in Woha District. The design compared the GGE and CLIS learning models with students’ initial motivation levels (high/low) as a moderating factor. Data were analyzed using one-way ANOVA, Kruskal–Wallis, and post hoc Tukey tests. The results show a significant difference (p < 0.05) between the two learning models in enhancing students’ motivation and learning outcomes, with the GGE learning model proving to be more effective than CLIS. This research concludes that the combination of cooperative learning models with practical methods such as Jarimatika is an effective strategy to improve the quality of mathematics learning in elementary schools.